Novel Triazole Thiole ligand and some of its metal chelates: Synthesis, structure charactertization, thermal behavior in comparison withcomputational caculations andbiological activities. (February 2019) - Zayed, Ehab M.; Zayed, M.A.; Abd El Salam, Hayam A.; Noamaan, Mahmoud A.
Graphical abstract: Highlights: Novel (HL) triazole-thiole ligand and its metal chelates of octahedral geometry [MHL2 ].2H2 O, M = Fe(III), Co(II), Ni(II) were prepared and characterized They were characterized by elemental analyses, FT-IR, NMR, magnetic moment, molar conductance, and thermal analyses. The geometries of triazole-thiole ligand and its metal chelates were fully optimized using B3LYP method; DFT/GENECP level by Def2TZVP and 6-311++G (d, p) basis sets. Their structures are confirmed by successful correlation between experimental and theoretical calculations. The ligand and its metal chelates had been examined against different kinds of bacteria and fungi to examine their antimicrobial biological activity and molecular docking. Abstract: Structural and molecular properties of HL, 4-amino-5-(2, 2-dichloro-1-methylcyclopropyl)-4H-1, 2, 4-triazole-3-thiol toward the transition metal ions namely Fe(III), Co(II) and Ni(II) had been studied using elemental analyses, magnetic, electronic, FT- IR, 1 H-NMR and Thermal analyses (TGA and DTA). The interpretation of thermal decomposition stages had been evaluated. The computations had been done by software of Gaussian 09W package. The geometries of triazole-thiole ligand and its metal chelates were fully optimized using density functional theory B3LYP method. (DFT)/GENECP level by implementing Def2TZVP basis set was used for Fe, Co and Ni-atoms; and basis set 6-311++G (d, p) was used for remainder atoms. There are no symmetry constrains had been applied during geometry optimization. The mixed basis set was selected due to its flexibility. HOMO and LUMO energy values for chelates, chemical hardness and electronegativity had been calculated. NBO calculations had been done at the same level using (NBO 3.1) program involved in the software of Gaussian 09W for measurement qualitatively the intra-molecular delocalization in systems under investigation. The first 15, 85, 65 and 65 low-lying excited states for ligand and Fe, Co and Ni chelates respectively had been calculated within the vertical linear-response. TD-DFT approximation at the same level of theory was used to calculate the electronic absorption spectra of the studied compounds. Their structures are confirmed by successful correlation between experimental and theoretical calculations. The ligand and its metal chelates had been examined against two bacteria such as Gram-positive ( Staphylococcus aureus ATTC 12600), GraM–Negative ( Escherichia coli ATTC 11775) and two fungus ( Aspergillus flavus and Candida albicans ) and molecular docking using Auto Dock tools were utilized.